Glycated Haemogloin, Fasting Plasma Glucose, Plasminogen Activator Inhibitor Type-1, and Soluble Thrombomodulin Levels in Patients with Type 2 Diabetes Mellitus (Nigerian Journal of Physiological Sciences, 2021)
Diabetes mellitus has become increasingly prevalent over the years. The chronic hyperglycaemia of diabetes is associated with long-term damage, dysfunctions, and failure of different organs suggesting that the most effective tool to prevent complications is the effective control of hyperglycaemia itself. The study is set to determine the effect of glycemic control on plasminogen activator inhibitor type 1 (PAI-1), soluble thrombomodulin (STM) alongside fasting plasma glucose (FPG) and glycated hemoglobin (HbA1c) among type 2 diabetic subjects. One hundred diabetic subjects accessing care at the University of Calabar Teaching Hospital Calabar and 100 non –diabetics that served as controls were enrolled. Blood samples from participants were analyzed for FPG, HbA1c, PAI-1 and STM by standard methods. The result shows 74% of the diabetic to be females. Half of the diabetics were managed on only oral anti-diabetic drugs while the remaining half were either on insulin injection or a combination of oral and insulin injection.  Poor glycemic control was observed in 56% of the studied subjects. The mean age of 54.69 ± 9.94 years for the diabetics was comparable to the age-matched controls (p=.097). Diabetics showed significantly higher FPG, HbA1c, PAI-1and STM (P=0.001) compared to control values. Correlations between STM, PAI 1 and glycated hemoglobin (figures 2 p=0.001, p =0.001) and STM, PAI-1 and FPG revealed significantly robust association (p=0.001, p=0.001).  The study concludes that there is poor glycemic control among the treated diabetic subjects with PAI-1 and STM showing a very strong positive correlation with HbA1c than FPG.